NILAI AKHLAK DALAM BUKU SALEH RITUAL, SALEH SOSIAL KARYA A. MUSTOFA BISRI - Faridatul Ulya; Rosichin Mansur; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Moral is an important thing in building a good human personality. The description of someone’s inner condition is the nature of morals. However, people today pay little attention in implementing moral values in their daily life. From the book entitled “Saleh Ritual Saleh Sosial” tells about the life of society today which is ac ondition where they know about themselves and their God but their caring for others decreases. The action in worship is just a meaningless action due to reach maqam muttaqi must include ritual and social piety. So that the worship value to Allah has a positive influence on human moral values for the survival of society.